Праздники народов Удмуртии. 2006 год: [календарь] / [М-во нац. политики УР - Смирнова Н. П. (Пешта, 2005)
Экземпляры: КР (20060727) / Инвентарный номер: у60553 / Цена: 30.00 / Сис.шифр: 63.5 / Авт.знак: П 68 / ГРНТИ: 03 / ББК: 63.529(235.5)